Toxic Effect Of Cypermethrin On Enzymes In Freshwater Fish Oreochromis mossambicus (Tilapia): Life Sciences-Cypermethrin toxicity onEdible Fresh water Fish - K. K. Kalpana Devi; J.Prakash Sahaya leon (International Journal of Life Science and Pharma Research, 2022)
In agriculture, excessive use of various pesticides had increased in developing countries. These pesticides may be highly toxic, not only to aquatic organisms like fishes but also to humans. In recent years, synthetic pyrethroids were developed for major uses in various agriculture practices and public health purposes. We aim to find the toxic Effect of Cypermethrin on Freshwater Fish Oreochromis mossambicus(Tilapia). The fish Oreochromis mossambicus were exposed for 30 days to various sub lethal concentrations (1/10, 1/20, and 1/30) of cypermethrin. After completion of a 30 days exposure, the fish Oreochromis mossambicus was sacrificed and tissue samples of muscle, liver, and kidney were analyzed. Decreased value of ALP, ACP, and Increased value of AST, ALT was observed in all the sub lethal exposure of cypermethrin on treated freshwater fish Oreochromis mossambicus at 30 days on comparing with the control group. High variation of AST and ALT were observed in the liver at 1/10th concentration of cypermethrin and elevated variation of ALP and ACP was observed in the liver at 1/10th concentration of sub lethal level for 30 days exposure. While comparing with the control group, the effects of cypermethrin on experimental fish showed increased levels of AST, ALT in the tissues of muscle, liver, and kidney of O. mossambicus, and the level of ACP and ALP were found in a decreased manner. Increased levels of ALT and AST activity observed in freshwater fishes may be due to the reduction of metabolic activity and concentration of ACP and ALP in various tissues due to cellular necrosis. In the present study, we found that the effect of cypermethrin alters the activity of various enzymes in freshwater fish Oreochromis mossambicus. It is concluded from this study that exposure to cypermethrin affects the enzyme activities of fish.